2011
DOI: 10.1556/amicr.58.2011.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mammalian codon usage of fimH in DNA vaccine design

Abstract: Uropathogenic Escherichia coli (UPEC) bacteria are the principal cause of urinary tract infections (UTI). Because these bacteria propagate intracellularly, the cellular immune response is an important factor in UTIs. Therefore, we designed a genetic construct to induce a cellular immune response. In order to develop a genetic construct that induces strong cellular immunity against this pathogen, we used the fimH synthetic gene according to mammalian codon usage, and the gene expression was compared with wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In addition to the use of optimized codons, several studies [32–34] have also reported that the expression and ELISA titer of synthesized genes markedly increased upon the removal of rare codons and unstable sequences. Bagherpour et al synthesized fimH of Uropathogenic Escherichia coli ( UPEC ) using mammalian codons [35]. Compared with the wild-type gene, the fimH gene of the mammalian codon has been shown to be compatible with eukaryotic expression systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use of optimized codons, several studies [32–34] have also reported that the expression and ELISA titer of synthesized genes markedly increased upon the removal of rare codons and unstable sequences. Bagherpour et al synthesized fimH of Uropathogenic Escherichia coli ( UPEC ) using mammalian codons [35]. Compared with the wild-type gene, the fimH gene of the mammalian codon has been shown to be compatible with eukaryotic expression systems.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids pVAX/ fim H(mam) and pVAX/ fim H(wt) were constructed in our laboratory as described previously [14]. Briefly, fim H(mam) comprised of mammalian (mam) codon usage sequences of Fim H protein and fim H(wt) composed of wild type (wt) codon usage sequences of FimH protein.…”
Section: Methodsmentioning
confidence: 99%
“…Electoporation delivery system was used to enhance host immune responses. In an independent study [14], we confirmed the expression of current DNA vaccine in vitro ; in the present study, we intended to examine the induction of cellular immunity against recurrent UTI in response to DNA vaccine in BALB/c mice.…”
Section: Introductionmentioning
confidence: 93%
“…Immunization resulted in T H 1 and T H 2 responses as assessed by cytokine responses in splenocyte proliferation assays and ratio of IgG1 to IgG2a. Lastly, another group has recently developed a mammalian codon-optimized fimH plasmid construct that could be used in a DNA vaccine, but they have not published results of trials in animals (312). …”
Section: Uti Vaccinesmentioning
confidence: 99%